PENGEMBANGAN PENUNTUN PRAKTIKUM IPA BERBASIS YOUTUBE UNTUK MENINGKATKAN PELAKSANAAN PRAKTIKUM PADA MAHASISWA - Setiawati, Gusti Ayu Dewi; Jaya, I Ketut Manik Asta; Witraguna, Kadek Yudista (STKIP PGRI Situbondo, 2025)
One of the most important methods in Natural Sciences learning is practicum. The problem faced by the Department of Primary School Teacher Education, I Gusti Bagus Sugriwa State Hindu University, Denpasar, is that the implementation of science practicums has not been optimal due to the absence of science practicum guides and facilities. The solution to this problem is developing practicum implementation by providing practicum guides that are able to facilitate existing limitations. This research uses research and development methods that aims to develop a science practicum guide starting from exploring science material to developing a YouTube-based science practicum guide to enhance student practicum implementation. Results showed that the validity test results gained validity score of 89% which means valid. After being applied to students, they also received responses in the categories of strongly agree and agree. Thus, showed that the practicum guide utilizable as a supplement in teaching materials so as to support the improvement of practicum implementation among students.